Analysis of Indonesian Tourism Demand by Foreign Tourist in ASEAN Region - Jasmine Abqoriyyah Haryanto; Neli Agustina (PROGRAM STUDI PARIWISATA SYARAH, FAKULTAS EKONOMI DAN BISNIS ISLAM, UNIVERSITAS ISLAM NEGERI MATARAM, 2025)
Purpose: This study aims to assess the overall pattern of ASEAN tourist visits to Indonesia and investigate the potential driving tourism demand between 2017 to 2022. The study focuses on variables believed to influence ASEAN travelers’ interest in Indonesia, such as per capita income, relative pricing, substitution prices, currency exchange rates, and population size. Method: This study employs panel data covering 9 ASEAN countries—excluding Indonesia and Timor Leste—namely Malaysia, Singapore, Thailand, the Philippines, Laos, Brunei Darussalam, Vietnam, Cambodia, and Myanmar, as the cross-sectional units over the period from 2017 to 2022. The analysis is based on secondary data sourced from BPS, UNCTAD, and the World Bank. The dependent variable is the number of tourists from ASEAN countries. Panel data regression is utilized to identify the factors influencing the demand for tourism in Indonesia by ASEAN visitors during the 2017–2022 Result: The result of the study indicate that the population and per capita income of ASEAN nations have a significant positive impact on ASEAN travelers' demand for travel to Indonesia. In contrast, the fluctuating cost of substituting Indonesian travel with travel to Malaysia, Singapore, and Thailand has a significantly negative impact on the demand for Indonesian tourism. The relative price variable and the Rupiah exchange rate do not significantly impact the demand for Indonesian tourism by ASEAN travelers. Contribution: The main contribution of this research is a recommended government policy aimed at maintaining price stability in Indonesia to enhance its competitiveness within the ASEAN region. Additionally, efforts should be made to promote domestic tourism through social media campaigns and to enhance the quality and service standards of the tourism sector to boost Indonesia’s appeal. Ensuring currency stability involves implementing a combination of economic and monetary policies, such as balancing currency supply and demand, maintaining macroeconomic stability, managing inflation, and fostering both domestic and foreign investment.